UJI KELAYAKAN MEDIA MIND MAPPING MOTIVASI BELAJAR - Komariah, Euis Siti; Rohaeti, Euis Eti; Septian, Muhammad Rezza (IKIP Siliwangi, 2023)
This article aims to determine the feasibility test of mind mapping media in group guidance on the learning motivation of class VIII students of SMPN 2 Rancaekek. This article is part of research and development or Research and Development (R&D) according to Borg and Gall which includes an assessment of the feasibility test of material experts, media experts and expert guidance and counseling teacher practitioners. The data collection technique in this development research is through a questionnaire/instrument. The data obtained from the instrument questionnaire were analyzed descriptively qualitatively and quantitatively. The results of this study indicate that; The feasibility test of mind mapping media is assessed based on; a. Material experts get a total score of 70 with a percentage of 97.2% which is in the very feasible category, b. Media experts get a total score of 96 with a percentage of 96% being in the very decent category, and c. Expert practitioners get a total score of 96 with a percentage of 96% that fall into the very decent category. which can be concluded that the learning motivation mind mapping media product is very feasible to be used in the group guidance service process.